DEHYDRATION AND HIDRO REPOSITION DURING JUDO TRAINING (Fiep Bulletin - online, 2014)
The fluid replacement during the sporting practice is fundamental for a good performance. The aims of this study were: identify the dehydration induced by the judo training with duration of 60 minutes and if the consumption of liquids ad libitum is enough to avoid this dehydration. Participated of this study 15 male judokas (medium age 22.07 ± 2.05 years and body weight 78.35 ± 8.89kg). The athletes were appraised in six trainings accomplished in alternate days. In the first 3 trainings the judokas were not hydrated. And, in the other trainings they were supplied with water and carbohydrate solution to hydrate ad libitum. According the results, a session of judo training with 60 minutes of duration imposes the athlete's loss of weight close to 2% (approximately 1.5kg for the sample). The athletes, even with reposition themselves finished the trainings with superior dehydration to 1%. It is concluded that a training of judo of 1 hour of duration, imposes a hydric loss of 2% of body weight and that the hydration model adopted (ad libitum) was not enough to maintain the homeostasis of the judokas, it is recommended to adopt regular intervals of hydration.
Keywords: hydration; judo; body weight